THE USE OF DIGITAL TECHNOLOGIES IN DEVELOPING STUDENTS’ COMMUNICATIVE COMPETENCE IN ENGLISH LANGUAGE TEACHING - Berdiqulova Mahbuba Erkinon qizi; Tolipova Nilufar Jaxongir qizi (TADQIQOTLAR, 2026)
ABSTRACT This article examines the role of digital technologies in developing students’ communicative  competence  in the process  of teaching  English  in higher  education institutions.  The  study  analyzes  the  impact  of  modern  digital  tools,  including multimedia  resources,  online  platforms,  and  interactive  applications,  on  improving students’ speaking, listening, reading, and writing skills. Special attention is paid to the importance  of  digital  technologies  in  increasing  students’  motivation,  independent learning abilities, and active participation in the educational process. The article also identifies  existing  problems  related  to  the  use  of  digital  technologies,  such  as insufficient  digital  competence  of  teachers  and  technical  limitations.  Based  on  the analysis of scientific literature and pedagogical practice, practical recommendations are proposed for the effective integration of digital technologies into English language teaching. The results show that the use of digital technologies contributes to improving the quality of education and the development of students’ communicative competence.